Multiple Palaeoproterozoic carbon burial episodes and excursions - Martin, A.P.; Prave, A.R.; Condon, D.J.; Lepland, A.; Fallick, A.E.; Romashkin, A.E.; Medvedev, P.V.; Rychanchik, D.V. (Earth and Planetary Science Letters, 2015)
Organic-rich rocks (averaging 2–5% total organic carbon) and positive carbonate-carbon isotope excursions (δ 13 C > 5‰ and locally much higher, i.e. the Lomagundi-Jatuli Event) are hallmark features of Palaeoproterozoic successions and are assumed to archive a global event of unique environmental conditions following the c. 2.3 Ga Great Oxidation Event. Here we combine new and published geochronology that shows that the main Palaeoproterozoic carbon burial episodes (CBEs) preserved in Russia, Gabon and Australia were temporally discrete depositional events between c. 2.10 and 1.85 Ga. In northwest Russia we can also show that timing of the termination of the Lomagundi-Jatuli Event may have differed by up to 50 Ma between localities, and that Ni mineralisation occurred at c. 1920 Ma. Further, CBEs have traits in common with Mesozoic Oceanic Anoxic Events (OAEs); both are exceptionally organic-rich relative to encasing strata, associated with contemporaneous igneous activity and marked by organic carbon isotope profiles that exhibit a stepped decrease followed by a stabilisation period and recovery. Although CBE strata are thicker and of greater duration than OAEs (100 s of metres versus metres, ∼10 6 years versus ∼10 5 years), their shared characteristics hint at a commonality of cause(s) and feedbacks. This suggests that CBEs represent processes that can be either basin-specific or global in nature and a combination of circumstances that are not unique to the Palaeoproterozoic. Our findings urge circumspection and re-consideration of models that assume CBEs are a Deep Time singularity.